Co-Branding Strategy in Cross-Industry Business: A Case of Mobile Games and Food Products Collaboration on Indonesian Mobile Games Players - Sagita, Refina Dara Nur; Said, Laila Refiana (Program MM Universitas Surabaya, 2024)
Purpose: This study discusses the cross-industry co-branding strategy of PUBG (Player Unknown's Battle Grounds) Mobile x Indomie products by analyzing the influence of self-congruity and brand fit variables on co-branding and its impact on brand equity and purchase intention carried out on mobile game players in Indonesia. Method: This study used quantitative research methods with the population of Indonesian mobile game players. The study used purposive sampling with a sample of 180 respondents. Data was processed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 3.0 software. Result: The results of this study prove that co-branding is influenced by brands that have more value and appeal and are influenced by brand combinations that match both symbolic and functional effects. Co-branding with a combination of brands with an equivalent level of equity shares the benefits of co-branding equally, so co-branding with a combination of high and low-equity brands is believed to influence brand equity significantly. Good co-branding will provide a positive evaluation of a brand to encourage consumer purchase intention.